Integrated asssesment of the Klang River water quality for enviromental management - Mohamad Hasan, Raja Aznn (2017)
The Klang River is an essential river for Klang Valley residents since there are two major dams at upstream of the river known as Batu Dam and Klang Gates Dam. This dam function as main water supply to the people of Klang Valley. Hence, it is essential to monitor the water quality by test the water regularly in order to maintain safe and reliable sources of water for the residents. The research is mainly about to determine the water quality of the Klang River via physical, chemical and biological test based on National Water Quality Standards (NWQS) and Water Quality Standards (WQI). Besides, it also focus on to identify the sources of contamination, recommend precautions and actions to take to consider the level of water quality. The 10 parameters that need to be determined are in-situ parameter such as pH, dissolved oxygen (DO), electrical conductivity, turbidity, temperature and ex-situ parameter such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), ammoniacal-nitrogen(NH3-N) and presence of selected heavy metal. The Klang river water samples was taken from three point based on land use pattern. The sample were taken twice where sunny days during first sampling and rainy days during second sampling. The testing was done at UMP Environmental Lab of Faculty of Civil Engineering and Earth Resources. The presence of heavy metal were traced by using Atomic Absoption Spectroscopy (AAS) while presence of Ammonia Nitrogen was carried out based on the Standard Method APHA 4500-NH3-BC. The test of TSS was carried out based on Standard Method APHA 2540-D and COD was carried out based on Standard Method APHA 5220-C. The presence of ammonia nitrogen was higher where it was between 7 – 13 mg/L during first sampling and 9 – 17 mg/L during second sampling. It supposed in range of 0.3 – 0.9 mg/L in order to classified it in class III. Besides, TSS showed higher reading where the range was in between 200 – 300 mg/L. It supposed to be in the range of 50 – 150 mg/L for Class III river. However, the other parameter are such as BOD,DO,COD, and pH showed in range of class III according to NWQS. The research found that Klang River water quality is currently in class III based on NWQS. It needs extensive treatment in order to use as water supply. The recommendation action to taken are installing additional gross pollutant traps, install more wastewater more treatment plant especially at more pollution area besides promote and manage river cleanliness.